Determining the Minimally Important Difference in the Clinical Disease Activity Index for Improvement and Worsening in Early Rheumatoid Arthritis Patients. Issue 10 (October 2015) - Curtis, J. R.; Yang, S.; Chen, L.; Pope, J. E.; Keystone, E. C.; Haraoui, B.; Boire, G.; Thorne, J. C.; Tin, D.; Hitchon, C. A.; Bingham, C. O.; Bykerk, V. P.
<x xml:space="preserve">Abstract</x> Objective Simplified measures to quantify rheumatoid arthritis (RA) disease activity are increasingly used. The minimum clinically important differences (MCID) for some measures, such as the Clinical Disease Activity Index (CDAI), have not been well‐defined in real‐world clinic settings, especially for early RA patients with low/moderate disease activity. Methods Data from Canadian Early Arthritis Cohort patients were used to examine absolute change in CDAI in the first year after enrollment, stratified by disease activity. MCID cut points were derived to optimize the sum of sensitivity and specificity versus the gold standard of patient self‐reported improvement or worsening. Sensitivity, specificity, positive predictive values, and negative predictive values were calculated against patient self‐reported improvement (gold standard) and for change in pain, Health Assessment Questionnaire (HAQ), and Disease Activity Score in 28 joints (DAS28) improvement. Discrimination was examined using the area under receiver operator curves. Similar methods were used to evaluate MCIDs for worsening for patients who achieved low disease activity. Results A total of 578 patients (mean ± SD age 54.1 ± 15.3 years, 75% women, median [interquartile range] disease duration 5.3 [3.3, 8.0] months) contributed 1, 169 visit pairs to the improvement analysis. The MCID cut points for improvement were 12 (patients starting in high disease activity: CDAI >22), 6 (moderate: CDAI 10–22), and 1 (low disease activity: CDAI <10). Performance characteristics were acceptable using these cut points for pain, HAQ, and DAS28. The MCID for CDAI worsening among patients who achieved low disease activity was 2 units. Conclusion These minimum important absolute differences in CDAI can be used to evaluate improvement and worsening and increase the utility of CDAI in clinical practice.